View of the late Rev. Charles Skelton's Meeting House adjacent to site of the Globe Theatre, Maid Lane, Southwark - Stow, James; Shepherd, G. (Tufts Archival Research Center, 2008)
With a plan of the spot, Skelton's Monument, and a view of a mill erected on the basement of the Meeting House. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.